Modulation of proteostasis and protein trafficking: a therapeutic avenue for misfolded G protein-coupled receptors causing disease in humans. Issue 1 (13th March 2019) - Ulloa-Aguirre, Alfredo; Janovick, Jo Ann
Abstract: Proteostasis refers to the process whereby the cell maintains in equilibrium the protein content of different compartments. This system consists of a highly interconnected network intended to efficiently regulate the synthesis, folding, trafficking, and degradation of newly synthesized proteins. Molecular chaperones are key players of the proteostasis network. These proteins assist in the assembly and folding processes of newly synthesized proteins in a concerted manner to achieve a three-dimensional structure compatible with export from the endoplasmic reticulum to other cell compartments. Pharmacologic interventions intended to modulate the proteostasis network and tackle the devastating effects of conformational diseases caused by protein misfolding are under development. These include small molecules called pharmacoperones, which are highly specific toward the target protein serving as a molecular framework to cause misfolded mutant proteins to fold and adopt a stable conformation suitable for passing the scrutiny of the quality control system and reach its correct location within the cell. Here, we review the main components of the proteostasis network and how pharmacoperones may be employed to correct misfolding of two G protein-coupled receptors, the vasopressin 2 receptor and the gonadotropin-releasing hormone receptor, whose mutations lead to X-linked nephrogenic diabetes insipidus and congenital hypogonadotropic hypogonadism in humans respectively.